Diffusion-Weighted Magnetic Resonance Diagnosis of Local Recurrences of Prostate Cancer after Radical Prostatectomy: Preliminary Evaluation on Twenty-Seven Cases. (16th February 2014) - Carbone, Salvatore Francesco; Pirtoli, Luigi; Ricci, Veronica; Carfagno, Tommaso; Tini, Paolo; La Penna, Augusto; Cacchiarelli, Eleonora; Volterrani, Luca
Abstract : Objectives. To assess the diagnostic performance of diffusion-weighted MR imaging (DWI) in patients affected by prostatic fossa (PF) relapse after radical prostatectomy (RP) for prostatic carcinoma (PC). Methods. Twenty-seven patients showing a nodular lesion in the PF at T2-weighted MR imaging after RP, with diagnosis of PC relapse established by biopsy or PSA determinations, were investigated by DWI. Two readers evaluated the DWI results in consensus and the apparent diffusion coefficient (ADC) of the nodules, separately; a mean value was obtained (ADCm). Results. Relapses did not significantly differ in size in respect of postsurgical benign nodules. The DWI qualitative evaluation showed sensitivity, specificity, accuracy, ppv, and npv values, respectively, of 83.3%, 88.9%, 85.2%, 93.7%, and 72.7% (100%, 87.5%, 95.6%, 93.7%, and 100%, for nodules >6 mm). The intraclass correlation coefficient (ICC) for ADC evaluation between the two readers was 0.852 (95% CI 0.661–0.935; P = 0.0001 ). The ADCm values for relapses and benign nodules were, respectively, 0.98 ± 0.21 × 10 − 3  mm 2 /sec and 1.24 ± 0.32 × 10 − 3  mm 2 /sec (P = 0.006 ). Sensitivity, specificity, accuracy, ppv and npv of ADCm were, respectively, 77.8%, 88.9%, 81.8%, 93.3%, and 66.7% (93.3%, 87.5%, 85.4%, 93.3%, and 87.5% for nodules >6 mm). Conclusions. Diffusion-weighted MR imaging is a promising tool in the management of a hyperintense nodule detected by T2-weighted sequences. This might have a relevant importance in contouring radiotherapy treatment volumes.